Analisis Pengaruh Inflasi, Suku Bunga, Nilai Tukar, dan Jumlah Uang Beredar, Terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2013-2022 - Sari, Indra; Az Zakiyyah, Nurul Azizah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Composite Stock Price Index (IHSG) is a unit index based on all types of shares traded on the stock exchange or stock market. The capital market plays a big role in a country's economy because it can influence and also encourage companies to develop. The role of the capital market in a country is as a driving force for the economy, because the capital market is a means of investing funds in the long term. Every country has a capital market that moves every day as seen from the fluctuating share prices. One of the indicators that causes movements in the Composite Stock Price Index (IHSG) is macroeconomic indicators. In the following research, the macroeconomic indicators used are inflation, exchange rates, interest rates and money supply. These macroeconomic indicators are fluctuating. This research aims to find out what the long-term and short-term influence of macroeconomic factors, namely inflation, interest rates, exchange rates and money supply on the IHSG. The research data used is time series data from the macroeconomic variables mentioned as well as IHSG data taken from 2013-2022 (monthly) and obtained from the Central Statistics Agency (BPS), Financial Services Authority, and Bank Indonesia (BI). The data that has been obtained is processed using the Eviews 10 analysis tool and the method used is the Vector Error Correction (VECM) method.